PEMBERDAYAAN KELOMPOK TANI TERNAK DALAM PENERAPAN TEKNOLOGI MESIN PENCACAH RUMPUT ALTERNATIF UNTUK PAKAN TERNAK KAMBING DI DESA KOLAM KEC. PERCUT SEI TUAN - Suhardi Napid; Rahmad Setia Budi; Abdul Haris Nasution; Rachmat Rizaldi; Fikriansyah Fikriansyah (Jurnal Pengabdian Mitra Masyarakat, 2023)
One of the potential livestock commodities to be developed is goats. A number of problems faced by goat breeders include seed quality, feed supply, disease prevention, market expansion to increase production. However, the main problem of discussion is the availability of animal feed. Currently goat breeders are still experiencing a problem in the supply of animal feed as a source of protein. Breeders must provide grass in sufficient quantities to be chopped as livestock feed. Most breeders still use the conventional grass chopping process. Farmers in the Pond Village area still use sickles to get grass which has to provide large amounts of grass as the number of goats also increases, therefore it takes more time and effort. The solution to solving the problems faced is to approach partners so that alternative grass chopping technology can be accepted and implemented. With the application of alternative grass chopping machines, smaller pieces of grass are obtained to be given as animal feed so that it is easier for livestock to digest the food. As the prime mover of this grass chopper is an electric motor and a gasoline engine. If the location is available a source of electric current can use an electric motor dynamo. If the conditions where the livestock is far from the reach of electricity can use a gasoline engine. Alternative grass chopper with consequences can increase livestock feed production capacity. Transferring the function of using a scythe as a grass chopping tool to chopping grass using a machine will ensure a quick time and an increase in production capacity which has been proven to work in the Kesuma cattle farming group. The grass chopper application is well supported/welcomed by the farmer group members, it is hoped that the farmer group residents will continue to use this chopper application.